Challenges for the incorporation of metrics in social determinants of health approaches - Jaiberth Antonio Cardona Arias; Walter Salas Zapata; Jaime Carmona Fonseca (Social Medicine Publication Group, 2021)
Public health has studied the relationship of morbidity and mortality to the living conditions of populations, with a greater focus on the individual level. In this context, an important theoretical advance was made in social determinants of health approaches (SDH), providing a way of explaining multiple socio-economic conditions that determine ways of living, of falling ill and of dying in specific populations. Despite advances in terms of its theoretical foundations, the methodological development of SDH approaches presents important lags in the metrics used, by: 1) erroneously functionalizing certain social constructs, 2) applying designs with risks of incurring fallacies (ecological, atomistic, sociological or psychological), or 3) applying designs that do not relate individual, particular and general measurements in a multilevel structure. Within this framework, this manuscript answers the question: what are the methodological challenges in the incorporation of metrics to SDH research, considering the need to articulate different levels of reality? In order to achieve this, it develops the following components: contextualization of SDH approaches, including the philosophical divergences and methodological convergences of its approaches, and the theoretical-conceptual foundations of ecological studies and multilevel analyses. Keywords: Social Determinants of Health; World Health Organization; Social Medicine; Ecological studies; Studies of population aggregates; Quantitative analysis; Multilevel analysis.